Experimental investigations on the effect of the spiral helical fins & flow channel routing inside flowing water stream on the heat exchanger performance in tropical environment. Issue 4 (8th August 2022) - Khan, Afrasyab; Sanaullah, Khairuddin; Regai Henry Rigit, Andrew; Zwawi, Mohammed; Algarni, Mohammed; Felemban, Bassem F.; Bahadar, Ali
ABSTRACT: The rapid economic growth of the Southeast Asian countries brought proportional stress on the air-conditioning sector. So, Ground Source Heat Exchangers (GSHE) is a cheap and efficient alternative for such air-conditioning units. Thermal performance of GSHE has optimised to determine the influence of variation in various parameters. The rate of heat transfer varied from 50.15 kW – 215.43 kW at varying mass flow rate 1–3 kg/m3s and 5–6 kg/m3s for hot and cold water. At a helix angle (i.e. 75 o, 82 0  and 89 0 ), the rate of heat transfer decreases ~29 – 4%. 20-2%, and 18-3% respectively. With increasing the rpm from 60 to 210, the rate of heat transfer reduced to 200 kW-35 kW, respectively. With the further increase from 210 to 360rpm, the rate of heat transfer reduced to 120–20 kW, respectively. By increasing the length of the circular base pipe up till 2 m, rate of heat transfers first went up till 250–75 kW and then reduced down to 130–40 kW. With increasing the length further up till 3 m, it first raised till 275–100 kW and then reduced till 150–70 kW.